EVALUATING SERVICE QUALITY AND PASSENGER SATISFACTION OF FEEDER BUSES IN URBAN PUBLIC TRANSPORTATION - Purwaningsih, Ratna; Putri, Ade Aisyah Arifna; Widharto, Yusuf; Fadli, Dinda Anggraini (J@ti Undip: Jurnal Teknik Industri, 2025)
Semarang faces congestion issues in land transportation, prompting the city government to introduce feeder buses connecting lower-demand areas to major transit hubs. The preliminary survey found that the number of passengers increased steadily. However, the increase in this number was accompanied by an increase in the number of passengers’ complaints. Thus, this study attempts to measure passenger satisfaction using the Consumer Satisfaction Index (CSI) and evaluates operational performance with the Importance and Performance Analysis (IPA) method. The literature review identified 14 aspects to measure passenger satisfaction, covering 28 attributes. Aspects needing improvement in quadrant I of the IPA analysis include vehicle condition, driver competency, and promptness of service providers in addressing complaints. Recommendations for improvement include adjusting departure intervals during peak and off-peak hours, implementing driver evaluation programs, conducting regular fleet inspections, and fostering customer engagement through forums.